Etika Penginjilan: Merekonstruksi Motivasi Menginjili Berdasarkan Pandangan Emmanuel Levinas dan John Stott dalam Konteks Masyarakat Multikultural - Wingki; Ferialdi Agasta; Desir Hendrik Panandu (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2023)
Indonesian society is a multicultur with complex problems. Religious sentimentality, racism, poverty, environmental damage are just a few examples of the problems that exist in society Indonesia. This also influences the way we carry out our Evangelism in situations like this. This research first describes the problems of multicultur society in Indonesian context, the explains the ethics of responsibility by Emmanuel Levinas and the Christian mission according to John Stott and ends with the ethical model of Levinas and Stott’s mission in the Indonesian context. This study uses qualitative methods by obtaining data from various literary sources, both books and journals and the most recent online news. From this research it can beunderstood that the Christian mission carried out must be in accordance with the context of the problems faced by other people or society. All of that must stem from the motivation to be responsible to God who sent us to carry out His mission in the world and responsibility for our encounters with other people or society to love their soul and bodies.